Stemming and lemmatization in English language classrooms - Tan, Jr., Jose G.; Caballero, Blessa Kay F. (Intelektual Pustaka Media Utama, 2026)
This study examines the pedagogical significance of linguistic features, stemming and lemmatization in enhancing vocabulary acquisition and retention in English language classrooms. It aims to provide teachers with insights that can inform and improve instructional practices. Specifically, the study addresses two key questions. Firstly, what linguistic features related to stemming and lemmatization are employed in English language classrooms? Secondly, how do these features contribute to vocabulary acquisition and retention? Using a qualitative research design, the study involved classroom observations and key informant interviews with nine teacher-participants from selected universities. The findings reveal that teachers actively integrate stemming and lemmatization as instructional tools to facilitate vocabulary learning. These techniques play a crucial role in helping students understand and retain new words. The study underscores the effectiveness of stemming and lemmatization in real-world classroom settings and highlights their value in enhancing vocabulary development. Integrating these linguistic strategies into teaching practices may optimize meaningful and effective English language learning experiences.